Electromagnetic Materials and Devices 2020
DOI: 10.5772/intechopen.82270
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Electromagnetic Interference Shielding Materials and Their Mechanisms

Abstract: Motivated by the increase of stress over electromagnetic pollution issues arising from the fast-growing development and need for electronic and electrical devices, the demand for materials with high electromagnetic interference (EMI) shielding performance has become more urgently. Considering the energy consumption in real applications, lightweight EMI shielding materials has been attentive in this field of research. In this chapter, first of all, the EM theory will be briefly discussed. Secondly, the EMI shie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…However, such material is designed to protect against ionizing radiation and is designed to replace lead. Study [7] suggested a material based on carbon and aerogel. However, at acceptable protective properties, the mechanical properties of coatings are unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…However, such material is designed to protect against ionizing radiation and is designed to replace lead. Study [7] suggested a material based on carbon and aerogel. However, at acceptable protective properties, the mechanical properties of coatings are unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the benefits and the potential risks need to be accessed judiciously. The problem of protection against high energy microwaves EM radiation is typical due to high intensity reciprocal interference of electronic instruments working in close proximity [1][2][3][4][5][6]. Furthermore, uncontrolled long-term exposure to these radiations imposes hazardous consequences on living organism creating potential health risk even jeopardizing their life [7].…”
Section: Introductionmentioning
confidence: 99%
“…These materials are widely used in radar applications, for solving problems of increased electromagnetic environment pollution (via design of electromagnetic compatibility (EMC) materials and components), metamaterials, etc. Nanomaterials based on different forms of carbon (carbon black, activated carbon, carbon fibers, nanotubes, graphene) are the most important components in the development of EMM due to the successful combination of their properties (electrical conductivity, chemical stability, and lightness) . Among these materials, aerogels of multiwalled carbon nanotubes (MWCNTs) combine the unique mechanical, thermal, and electrical properties of nanotubes with specific characteristics of aerogels (low density, high porosity, and large surface area) .…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials based on different forms of carbon (carbon black, activated carbon, carbon fibers, nanotubes, graphene) are the most important components in the development of EMM due to the successful combination of their properties (electrical conductivity, chemical stability, and lightness). [6][7][8][9][10] Among these materials, aerogels of multiwalled carbon nanotubes (MWCNTs) combine the unique mechanical, thermal, and electrical properties of nanotubes with specific characteristics of aerogels (low density, high porosity, and large surface area). [11] Due to the absence of a binder polymer, aerogels have the lowest density combined with high conductivity, which are unattainable for other classes of composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation